Macroeconomics and the LQ45 Index: Is the COVID-19 pandemic making a difference? - Lim Winny; Yulfiswandi Yulfiswandi (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2022)
This study examines how macroeconomic indicators and Covid-19 cases can affect the movement of the LQ45 index. The Covid-19 case was also studied as a moderator between the relationship between macroeconomic indicators and the LQ45 index to determine whether the Covid-19 case needed to be a crucial consideration when investing in stocks using macroeconomic indicator analysis techniques. This study was tested using multiple regression analysis methods. The results of the analysis found that the factors that were found to significantly affect the LQ45 index were the exchange rate which impacted the LQ45 index significantly negatively, the price of Brent oil, which involved the LQ45 index significantly negatively, the DJIA index, which positively affected the LQ45 index, and the case of Covid-19 which affects the LQ45 index significantly negatively. This study found two macroeconomic variables that had no significant effect on the LQ45 index: the inflation rate and real interest rates. Furthermore, the results has found a negative effect of the Covid-19 pandemic on the LQ45 index, so it is hoped that the government and investors can consider this research indicator as a consideration in making economic and investment decisions.